Empowerment of Women's Farmer Groups of “Kembang Lestari” in the Processing of Organic Waste from Various Fruit Peels as Liquid Fertilizer - A. A. S. P. R. Andriani; Made Ayu Gemuh Rasa Astiti; Ni Ketut Sri Rukmini (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
Partners in the implementation of Community Service is the Kembang Lestari Peasant Women's Group located in Taman Village, Abian Semal Subdistrict, Badung Regency. This group has problems with the high price of chemical fertilizers and vegetable pesticides for the treatment of cultivated crops. This condition causes an increase in production costs and decreased profits. They have yet to find a solution to get cheaper, environmentally friendly plant-based fertilizers and pesticides that they will use in their organic farms in the future. Therefore, it is necessary to provide an alternative to organic fertilizers while serving as vegetable pesticides that are easy to make, cheap, and environmentally friendly. The alternative is an eco-enzyme that can be made from organic waste in the form of fruit peels. Eco-enzymes have the same benefits as liquid fertilizers, compost, anti-bacterial, midges, and disinfectants. Women's Farmer Groups of Kembang Lestari are given knowledge of eco-enzymes and their benefits, how to make and how to apply them to plants. The methods carried out in the implementation of this activity are by interviewing, face-to-face, counseling, and practice methods directly. First, the authors held general counseling on what an eco-enzyme is, its benefits for plants, and environmental sustainability. Second, the authors provide hands-on training in the manufacture of eco-enzymes and how to implement them and conduct several evaluations to ensure farmers can make eco-enzymes independently and see what percentage of the increased production and increased profits earned by the farmer group after the implementation of these eco-enzymes. Third, it motivates farmers to keep using eco-enzyme fertilizers continuously in cultivating crops.